2013
DOI: 10.1371/journal.pone.0064921
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Epstein-Barr Virus Infection in U.S. Children Ages 6-19, 2003-2010

Abstract: BackgroundEpstein-Barr virus (EBV) is a common herpesvirus linked to infectious mononucleosis and multiple cancers. There are no national estimates of EBV seroprevalence in the United States. Our objective was to estimate the overall prevalence and sociodemographic predictors of EBV among U.S. children and adolescents aged 6–19.MethodsWe calculated prevalence estimates and prevalence ratios for EBV seroprevalence using data from the 2003–2010 U.S. National Health and Nutrition Examination Survey (NHANES) for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
161
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(187 citation statements)
references
References 34 publications
20
161
5
1
Order By: Relevance
“…The seroprevalence of EBV antibodies increases with age but varies across populations according to geographic region, ethnicity and socioeconomic status (Balfour et al, 2013;Condon et al, 2014;Dowd et al, 2013;Kagro et al, 1994). In the United States, a seroprevalence survey from 2009 found that around 50% of children between 6-8 years had antibodies against EBV (Balfour et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The seroprevalence of EBV antibodies increases with age but varies across populations according to geographic region, ethnicity and socioeconomic status (Balfour et al, 2013;Condon et al, 2014;Dowd et al, 2013;Kagro et al, 1994). In the United States, a seroprevalence survey from 2009 found that around 50% of children between 6-8 years had antibodies against EBV (Balfour et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted with students of Edinburg University, Higgins et al [12] determined seropositivity rates of 68.1% in males and 78.5% in females, which was a statistically significantly difference. In another study of children between 6-19 years of age, EBV seroprevalence was found to be higher in girls than in boys (68.9%, 64.2%) [13] . A study by Özkan et al [3] demonstrated that women had similar rates to men.…”
Section: Resultsmentioning
confidence: 88%
“…In contrast, Balfour et al [9] analyzed the relationship between family education level and seropositivity and found that seropositivity was 72% for those who did not attend high school, 63% for high school graduates, and 56% for those with education beyond high school. Another study showed that EBV seropositivity in individuals with education below high school, at the high school level, and beyond high school was 83.5%, 69.5%, and 59%, respectively [13] . As suggested by these studies, higher education level has been linked to better hygiene habits and consequently a lower risk of virus transmission.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are eight human herpesviruses and almost all adults are infected with at least one of these viruses [96][97][98][99][100][101][102]. Antiviral therapy is of great importance as herpesvirus infection in immunocompromised patients can evoke cancer or encephalitis and, therefore, death.…”
Section: Resultsmentioning
confidence: 99%